Maternal-Fetal Outcome, Lipid Profile and Oxidative Stress of Diabetic Rats Neonatally Exposed to Streptozotocin - Damasceno, Débora Cristina [UNESP]; Kiss, A. C. I. [UNESP]; Sinzato, Y. K. [UNESP]; Campos, Kleber Eduardo de [UNESP]; Rudge, Marilza Vieira Cunha [UNESP]; Calderon, Iracema de Mattos Paranhos [UNESP]; Volpato, Gustavo Tadeu [UNESP] (Johann Ambrosius Barth Verlag Medizinverlage Heidelberg Gmbh, 2011)
Background: There is no evidence about the integrated issue on glycemia, lipid profile, oxidative stress, and anomaly frequency of pregnant diabetic rats neonatally exposed to streptozotocin.Objective: Evaluating the impact of hyperglycemia in diabetic rats neonatally exposed to streptozotocin on maternal reproductive and fetal outcomes and the relationship with lipid profile and maternal oxidative stress.Material and Methods: Ten 90-day-old female Wistar rats were mated to obtain offspring. Some of these newborns received streptozotocin (70 mg/kg, i.p. - n5-STZ group) and the remainder given only citrate buffer (control group) on their day 5 of life. At adult life, these rats (n =13 animals/group) were mated and, at day 21 of pregnancy, they were killed to obtain a maternal blood samples for biochemical determinations. The gravid uterus was weighed with its contents and fetuses were analyzed.Results: At day 0 of pregnancy, glycemic means of n5-STZ rats were significantly greater compared to those of control rats, but presented fetuses classified as small for pregnancy age. The n5-STZ rats showed increased total cholesterol, triglycerides, MDA concentrations, lower SOD activity and increased frequency fetal visceral anomalies as compared to the control group.Conclusion: This study showed that the experimental model used led to mild hyperglycemia during pregnancy, although it did not lead to increased macrosomic fetus rates. The hyperglycemic maternal environment caused metabolic alterations, including increased triglyceride and total cholesterol concentrations, and elevated oxidative stress, contributing to increase fetal visceral anomalies.
Keywords: mild diabetes; streptozotocin; pregnancy; oxidative stress; anomaly; rat